LBA14Genomic HLA heterozygosity as a predictive marker for survival in lung cancer patients post immunotherapy. (24th November 2019) - Abed, A; Khattak, A; Millward, M; Chopra, A; Gray, E
Abstract: Background: We aimed to assess the role of genomic HLA-I/II heterozygosity in the overall survival benefit in patients with unresectable locally advanced, metastatic non-small lung cancer treated by PD1/L1 inhibitors. Methods: We collected blood from 170 advanced lung cancer patients treated with immunotherapy at two major oncology centres in Western Australia. High quality DNA was extracted from white blood cells and used for HLA-I/II typing. Information of tumour PDL1 status, pre-treatment neutrophil to lymphocyte ratio (NLR) and sex were identified. Each of those variables were correlated independently then in a multivariate analysis with OS. Correlation between HLA heterozygosity and response was assessed using Fisher exact. Patients with reduced or stable disease for 6 or more months were considered as responders. Results: Our data matured for 146 patients treated with anti-PD1/L1 therapy. We found that heterozygosity at all HLA-I loci had a favorable statistical trend towards better OS(HR = 0.5, P=0.06). However, heterozygosity at all HLA-II loci was not associated with OS(HR = 0.91, P=0.76). While response rate was higher amongst heterozygous patients especially at HLA-I (53.4% vs 45.6%), it was not statistically significant. NLR>5 was associated with statistically significant worse survival (HR = 2.22, P=0.009). This effect was driven by the patients with PDL1≥50% (HR = 3.86, P = 0.01 vs HR = 0.7, P = 0.5 for patients with PDL1<50%). Similarly, the effect of sex was seen mainly among patients with PDL1≥50%, with men more likely to have better OS than women (HR = 0.36, P = 0.06 vs HR = 1.1, P = 0.89 in the group of patients with PDL1<50%). A multivariate analysis showed that all three variables to be statistically significant predictors of survival. Conclusions: Our analysis suggest that OS among advanced lung cancer patients treated with immunotherapy is more likely to be influenced by homozygosity at HLA-I loci. Women with PDL1≥50%, NLR>5 and homozygous at ≥ 1 HLA-I locus possibly carries the worse prognosis when treated with immunotherapy alone and might benefit from treatment escalation. Editorial acknowledgement: A/Prof Elin Gray, Edith Cowan University, Western Australia. Legal entity responsible for the study: South Metropolitan Health Service - WA Health. Funding: Fiona Stanley Hospital (FSH) and Sir Charles Gairdner Hospital (SCGH) Disclosure: All authors have declared no conflicts of interest.